Oscillating infrared drying of apple peels - S. P. Rudobashta; D. O. Podyablonskaya; V. T. Kazub; L. A. Lago (Современная наука и инновации)
The oscillating infrared drying of Gala apple peel has been experimentally studied. The product has valuable nutritional properties and is in demand in the food industry. On the developed laboratory setup for studying the oscillating infrared drying process and maintaining the temperature of the dried material at a given temperature level, drying curves were obtained at three average material temperatures: t = 37 °C; 47 °C and 57 °C. OSRAM Siccatherm lamps were used as infrared radiation sources. The drying curves contained the first and second periods, the critical moisture content was equal to (kg moisture) / (kg dry material). As a result of the drying curves analysis, it was proposed to calculate the duration of the first period based on the drying rate, determined through the mass transfer coefficient, and the duration of the second period by generalizing the drying curves using the method of V.V. Krasnikov. For the studied material, the value of the relative drying coefficient (χ = 0.0624) was found, which allows implementing this method for the studied material. Data on the preservation of vitamin C in apple peel dried at different temperatures were obtained, which allows choosing the required temperature regime.